Unveiling the role of free DNA in biofilm formation; potential relevance in Cholera epidemiology - Afrid, Abir Hassan; Rahman, Mohammad Rafiue (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.